A Prospective Study of Serotonin and Norepinephrine Transporter Genes and the Response to Desvenlafaxine Over 8 Weeks in Major Depressive Disorder - Ng, C. H.; Bousman, C.; Smith, D. J.; Dowling, N.; Byron, K.; King, J.; Sarris, J. (Pharmacopsychiatry, 2016)
No studies to date have evaluated SLC6A2 and SLC6A4 genetic polymorphisms influencing antidepressant response to desvenlafaxine. We conducted an 8-week, open-label, prospective pilot study in 35 patients with major depressive disorder to assess the effects of genetic variations in SLC6A2 and SLC6A4 on both efficacy and side effect profile of desvenlafaxine. Results revealed that homozygotes for the SLC6A4 HTTLPR S allele showed a 33% HDRS reduction compared to a 58% reduction for L allele carriers (p=0.037). No results survived adjustments for covariates or multiple comparisons. While these results need to be interpreted cautiously, they provide preliminary support for the SLC6A4 HTTLPR polymorphism as potential modifier of desvenlafaxine efficacy.
Keywords: desvenlafaxine; antidepressant; pharmacogenetics; depression; SNRI